2023
DOI: 10.25122/jml-2021-0311
|View full text |Cite
|
Sign up to set email alerts
|

High levels of fecal calprotectin and C-reactive protein in patients with colitis

Abstract: Inflammatory bowel disease (IBD) with a poor prognosis may be due to persistent colitis. According to the latest guidelines, monitoring has become a part of the treatment process for colitis. Adequate monitoring of the patient's condition is necessary to determine the course of the disease to prevent the worsening of the condition and suppress the subclinical inflammatory process. This analytical study with a cross-sectional design was conducted to evaluate the activity of colitis using the results of C-reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Compared to fCal concentrations in a group of dogs with CIE (median: 92 μg/g; range: 0–638 μg/g; [ 24 ]) and fCal concentrations in human patients with ulcerative colitis (mean ± standard deviation: 132 ± 97 µg/g [ 55 ] or >130 µg/g [ 56 ]) or inflammatory bowel disease (IBD; mean ± standard deviation: 652.8 ± 799.7 µg/g or >50 µg/g [ 57 ]), fCal concentrations were lower in the CIE group of cats. A possible explanation for generally lower fCal concentrations in cats compared to humans is the predominance of a lymphoplasmacytic infiltrate in feline CIE [ 58 ] as opposed to neutrophilic granulocytes that express calprotectin and predominate in human IBD [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to fCal concentrations in a group of dogs with CIE (median: 92 μg/g; range: 0–638 μg/g; [ 24 ]) and fCal concentrations in human patients with ulcerative colitis (mean ± standard deviation: 132 ± 97 µg/g [ 55 ] or >130 µg/g [ 56 ]) or inflammatory bowel disease (IBD; mean ± standard deviation: 652.8 ± 799.7 µg/g or >50 µg/g [ 57 ]), fCal concentrations were lower in the CIE group of cats. A possible explanation for generally lower fCal concentrations in cats compared to humans is the predominance of a lymphoplasmacytic infiltrate in feline CIE [ 58 ] as opposed to neutrophilic granulocytes that express calprotectin and predominate in human IBD [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study also yielded an intriguing discovery: levels of IL-1β were significantly higher in male foetuses compared with female foetuses. IL-1β is a key immunoregulatory and pro-inflammatory cytokine that regulates IL-6 and TNF-α [ 95 , 96 ]. Research has indicated that in comparison to female foetuses, male foetuses' placentas are more prone to producing TNF-α, leading to a pro-inflammatory environment within AF [ 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…The fact that no correlation was found between FGF21 and CRP levels in UC patients may be related to quite wide range of CRP values in that group, particularly in active phase of disease. Additionally, it has been suggested that in UC, fecal calprotectin level has a better significance for detecting colitis compared to CRP ( Anindita et al, 2023 ). Noteworthy, other researchers ( Gariani et al, 2013 ) demonstrated a correlation between FGF21 level and CRP level in patients with systemic inflammatory response syndrome and had even proposed FGF21 as a non-specific marker for systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%